Interferon-α Enhances 5′-Deoxy-5-Fluorouridine-Induced Apoptosis by ERK-Dependant Upregulation of Thymidine Phosphorylase - Zhu, Yike (Hindawi Publishing Corporation, 2013)
5-Florouracil (5-FU) is the basic agent used in the treatment of gastric cancer. Capecitabine, a prodrug of 5-FU, displays increased antitumor efficacy compared with 5-FU in the clinic. 5′-Deoxy-5-fluorouracil (5′-DFUR), the metabolite of capecitabine, is converted to 5-FU by the enzyme thymidine phosphorylase (TP), which is present at high concentrations in human tumors. In this study, we investigated the effect of interferon-α (IFN-α) on the sensitivity of gastric cancer cells to treatment with 5′-DFUR and its relationship with TP expression. Preincubation of gastric cancer cells with IFN-α enhanced 5′-DFUR-induced apoptosis via IFN-α-mediated upregulation of TP. The depletion of TP with small interfering RNA (siRNA) obviously inhibited IFN-α-induced upregulation of TP expression and thus prevented apoptosis induced by IFN-α and 5′-DFUR. Treatment with IFN-α and combined IFN-α and 5′-DFUR treatment were also associated with concomitant activation of ERK signaling. Treatment with the ERK inhibitor PD98059 or depletion of ERK with siRNA partially reversed IFN-α-induced upregulation of TP expression, thus partially preventing apoptosis induced by IFN-α and 5′-DFUR. Taken together, our study shows that IFN-α enhanced 5′-DFUR-induced apoptosis in gastric cancer cells by upregulation of TP expression, which is partially regulated by activation of ERK signaling.